2003
DOI: 10.1046/j.1474-919x.2003.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat and weather are weak correlates of nestling condition and growth rates of four UK farmland passerines

Abstract: Agricultural intensification is believed to have driven declines of farmland bird populations and the invertebrates and weeds on which they feed. We investigated whether habitat and weather, as surrogates for food availability, influenced nestling growth rates and condition of four farmland passerines (Skylark Alauda arvensis , Chaffinch Fringilla coelebs , Linnet Carduelis cannabina and Yellowhammer Emberiza citrinella ). We also tested whether nestling growth rates or condition influenced whether a brood sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 34 publications
0
39
1
Order By: Relevance
“…Where nest failures occurred and the date was unknown, failure was assumed to have occurred at the mid-point between the two final visits to the nest. Where nests were discovered at the chick stage and age was unknown comparisons were made with the feather tract development of chicks of known age (as per Bradbury et al 2003). Nests were checked when chicks were 10 days old to determine fledging success; where a nest contained chicks at 7 days and the nest remained intact but was empty at 10 days (making predation of chicks immediately prior to fledging unlikely), the chicks were deemed to have fledged successfully.…”
Section: Fledging Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Where nest failures occurred and the date was unknown, failure was assumed to have occurred at the mid-point between the two final visits to the nest. Where nests were discovered at the chick stage and age was unknown comparisons were made with the feather tract development of chicks of known age (as per Bradbury et al 2003). Nests were checked when chicks were 10 days old to determine fledging success; where a nest contained chicks at 7 days and the nest remained intact but was empty at 10 days (making predation of chicks immediately prior to fledging unlikely), the chicks were deemed to have fledged successfully.…”
Section: Fledging Successmentioning
confidence: 99%
“…Nestling © 2010 British Trust for Ornithology, Bird Study, 57, 531-539 mortality in this species has been linked to weather variables such as cold temperatures and increased rainfall that decrease both numbers and activity levels of invertebrates (Bradbury et al 2003, Stoate et al 1998, and a reduction in the growth and body condition of chicks has been linked to the use of pesticides during the breeding season, through a decrease in invertebrate populations (Hart et al 2006, Morris et al . 2005.…”
mentioning
confidence: 99%
“…Yet, the relationship between food availability and nestling condition or survival is not consistently positive, perhaps because factors like accessibility, prey profitability and nutrient composition are not always accounted for. Although some studies found improved nestling weight and survival when food availability around the nest was higher, for example for Yellowhammer Emberiza citrinella (Hart et al 2006), Linnet Carduelis cannabina (Bradbury et al 2003) and Corn Bunting Miliaria calandra (Brickle et al 2000;Boatman et al 2004), other studies could not detect such correlations for Chaffinch Fringilla coelebs (Bradbury et al 2003), Yellowhammer (Bradbury et al 2003) and Yellow Wagtail Motacilla flava (Gilroy et al 2009). For Skylarks, there are indications that nestling condition is significantly affected by the abundance of chick food within 100 m of the nest (Boatman et al 2004).…”
Section: Skylark Reproductionmentioning
confidence: 80%
“…A possible explanation is that Skylark parents were able to compensate for a poorer environment by increasing their foraging efforts (Bradbury et al 2003;Gilroy et al 2009). When parents make longer or more frequent foraging flights, this can ultimately lead to reduced condition, elevated mortality rates or a reduced number of breeding attempts per year (Martin 1995;Siriwardena et al 2000).…”
Section: Skylark Reproductionmentioning
confidence: 99%
See 1 more Smart Citation